1997
DOI: 10.2307/3870384
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion in the PHYD Gene of the Arabidopsis Wassilewskija Ecotype Defines a Role for Phytochrome D in Red/Far-Red Light Sensing

Abstract: The PHYD gene of the Wassilewskija (Ws) ecotype of Arabidopsis contains a 14-bp deletion (the phyD-1 mutation) beginning at amino acid 29 of the reading frame, resulting in translation termination at a nonsense codon 138 nucleotides downstream of the deletion end point. Immunoblot analyses showed that Ws lacks phyD but contains normal levels of phyA, phyB, and phyC. By backcrossing into the Ws and Landsberg erecta genetic backgrounds, we constructed sibling pairs of PHYD+ and phyD-1 lines and of phyB- PHYD+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
198
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(209 citation statements)
references
References 0 publications
9
198
2
Order By: Relevance
“…Perhaps consistent with this is the fact that null mutants of these loci in Arabidopsis were not easily identified in genetic screens and the phenotypes of the monogenic mutants are not readily apparent (Aukerman et al, 1997;Devlin et al, 1998;Franklin et al, 2003;Monte et al, 2003). However, PHYC, D, and E have been retained much longer than the expected half-life of duplicate genes of ;3 to 7 million years (Lynch and Conery, 2000).…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 67%
See 1 more Smart Citation
“…Perhaps consistent with this is the fact that null mutants of these loci in Arabidopsis were not easily identified in genetic screens and the phenotypes of the monogenic mutants are not readily apparent (Aukerman et al, 1997;Devlin et al, 1998;Franklin et al, 2003;Monte et al, 2003). However, PHYC, D, and E have been retained much longer than the expected half-life of duplicate genes of ;3 to 7 million years (Lynch and Conery, 2000).…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 67%
“…Several plant species have two copies of PHYB (or P), including P. trichocarpa, maize, and members of Pinaceae, Solanaceae, Fabaceae, and Piperaceae. In Arabidopsis, phyB is the principal mediator of R-mediated development and shade avoidance, whereas phyD appears to play a minor role in shade avoidance; phyD-1 is a naturally occurring mutant, suggesting that phyD is dispensable in some environments (Aukerman et al, 1997). However, a recent study showing that the phyD null but not phyAphyB lost the ability to adjust the chlorophyll a/b ratio in response to canopy shading (Boonman et al, 2009) suggests that in shade avoidance, phyD but not phyB controls this response.…”
Section: Additional Phytochromes: An Expanded Role For the Phytochrommentioning
confidence: 99%
“…By analyzing the hypocotyl elongation under continous light conditions, a high-irradiance light response, it has been determined that PhyA is responsible for perceiving far-red light, whereas PhyB plays a primary role in perceiving red light (Quail et al, 1995). Recently, it has been shown that PhyD plays a minor role in mediating leaf expansion and stem elongation in conjunction with PhyB (Aukerman et al, 1997). Cry1 is a well defined blue-light receptor, mutations in which (hy4 mutants) cause a decrease in sensitivity to high-irradiance blue lightmediated inhibition of hypocotyl elongation (Ahmad and Cashmore, 1993;Lin et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…MABS analysis was performed by backcrossing the FN1148 mutant once to the same ecotype (Col-0) from which it originated to circumvent natural variation in ion accumulation between different ecotypes (see Introduction). Backcrossing into the parental ecotype also circumvented problems that could result from naturally occurring genomic deletion polymorphisms between two different ecotypes (12). F 2 mutants with Na ϩ overaccumulation phenotypes were identified by ICP, and a DNA pool was extracted from five of these individual F 2 mutant plants.…”
Section: Phenotyping Of Individuals In the Mapping Population Ismentioning
confidence: 99%